The Effect of Problem-Based Learning on Students’ Conceptual Understanding Reviewed from Students’ Beliefs - Mulyani, Nining; Tanti, Tanti; Murni, Pinta (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
This study aims to analyze the effect of the implementation of problem-based learning on the understanding of physics concepts in terms of students' beliefs. This study is a quasi-experimental study with a 2 x 2 factorial design. The research sample was 50 students from class XI IPA SMAN 10 Kota Jambi, and they were divided into an experimental class (n = 25) and a control class (n = 25). Data was collected using a four-tier diagnostic test, observation sheets, and a learning implementation checklist. The results of the analysis used a two-way ANOVA test. The study results showed that students in the experimental class had a higher percentage of conceptual understanding (66%) than students in the control class (50.8%). There was no influence of beliefs (positive and negative) on the knowledge of physics concepts. There was no interaction between the problem-based learning model and beliefs on students' understanding of physics concepts on static fluid material.